A Critical Evaluation of Anti-IL-13 and Anti-IL-4 Strategies in Severe Asthma - Diego Bagnasco; Matteo Ferrando; Gilda Varricchi; Giovanni Passalacqua; Giorgio Walter Canonica (2016)
Asthma is a high-prevalence disease, still accounting for mortality and high direct and indirect costs. It is now recognized that, despite the implementation of guidelines, a large proportion of cases remain not controlled. Certainly, adherence to therapy and the education of patients remain the primary objective, but the increasingly detailed knowledge about the pathogenic mechanisms and new biotechnologies offer the opportunity to better address and treat the disease. Interleukin (IL)-13 and IL-4 appear as the most suitable targets to treat the T helper 2 (TH2)-mediated forms (endotypes) of asthma. IL-13 and IL-4 partly share the same receptor and signaling pathways and both are deeply involved in immunoglobulin E (IgE) synthesis, eosinophil activation, mucus secretion and airways remodeling. Several anti-IL-13 strategies have been proposed (anrukinzumab, lebrikizunab and tralokinumab), with relevant clinical results reported with lebrikizumab. Such studies facilitate better definition of the possible predictive markers of response to a specific treatment (e.g. eosinophils, total IgE, fraction of exhaled nitric oxide and periostin). In parallel, anti-IL-4 strategies have been attempted (pascolizumab, pitakinra and dupilumab). So far, dupilumab was reported capable of reducing the severity of asthma and the rate of exacerbations. IL-13 and IL-4 are crucial in TH2-mediated inflammation in asthma, but it remains clear that only specific endotypes respond to these treatments. Although the use of anti-IL-14 and anti-IL-13 strategies is promising, the search for appropriate predictive biomarkers is urgently needed to better apply biological treatments.